Strategi Public Relations Muscle First dalam Membangun Brand Awareness Melalui Instagram - Rorencia, Vanessa Agnes; Wijaya, Lina Sinatra (Jurnal Pustaka Komunikasi, 2025)
To increase Muscle First brand awareness on social media, especially Instagram, Muscle First has diligently implemented a series of strategies to increase brand awareness. This research uses descriptive qualitative research with a case study method. Regarding the research instrument, it is by conducting interviews with several sources and observations made by the author conducting research on Muscle First's Instagram social media account regarding buyer responses. This determines Muscle First's image on public. Public Relations’ Muscle First uses strategies to increase brand awareness via Instagram via Key Opinion Leader (KOL) management. Muscle First's Key Opinion Leader (KOL) management uses a public relations strategy through four stages. The first stage is the planning stage, where market segmentation is carried out, content target planning, searching for the right Key Opinion Leader (KOL), and creating briefings. The second stage is the organizing stage, where the Key Opinion Leader (KOL) is organized, and a letter of cooperation is created. The third stage is the implementation stage, in which the key opinion leader (KOL) sends the content draft before finally uploading it to social media. The final stage is the monitoring stage, where Key Opinion Leader (KOL) management analyzes the Key Opinion Leader (KOL) Instagram insights and evaluates buyer responses to develop plans.